OPTIMIZATION OF DIGITAL TECHNOLOGY TO IMPROVE THE EFFICIENCY AND TRANSPARENCY OF LOCAL GOVERNMENT SERVICES IN INDONESIA - Widiasih, Suprapti; Julina, Faizah; Pratama Putra, Aditya (Irpia : Jurnal Ilmiah Riset dan Pengembangan, 2026)
Digital technology has become a key catalyst in improving the efficiency and quality of public services. Local governments, as the entities directly interacting with citizens, face major challenges in optimizing digital technology to meet the demands for efficiency and transparency in public services. This study aims to analyze the impact of digital technology implementation on enhancing the efficiency and transparency of public service delivery in Indonesia’s local governments. Using a literature review method, this research examines recent studies related to the adoption of e-Government, public service information systems, and the implementation of the Electronic-Based Government System (SPBE). The analysis shows that digital technology accelerates administrative processes, reduces operational costs, and increases public accountability. However, disparities in infrastructure and digital literacy remain key challenges, particularly in underdeveloped regions. With strong policy support, equitable infrastructure, and improved human resource capacity, digital transformation has significant potential to strengthen effective and transparent local governance. Keywords: digital technology, e-Government, public service efficiency, local government, SPBE